La apropiación como condición del derecho a la ciudad. El caso de la política de mejoramiento barrial de Villa Jardín, Municipio de Lanús, Buenos Aires - Jaime, Eugenia; Salvarredy, Julián (Pontificia Universidad Católica del Perú, 2023)
During the last twenty years, public policies for neighborhood improvement have been developed in the region with the purpose of urbanizing precarious settlements. However, these interventions have affected a relevant mass of inhabitants to fully develop their right to the city. On the other hand, the obstacles that faced the settlers to transit these processes in an appropriate manner are significant, according to Lefebvre's terms, as a condition for a just and democratic production.This article reflects, based on the work of the civil association Proyecto Habitar, in alliance with the Defensoría General de la Nación Argentina during 2018, on the role played by appropriation in urbanization processes that include population relocation, specifically the implementation of a public policy of neighborhood improvement in Villa Jardín - Lanús in Metropolitan Area of Buenos Aires. For the analysis, three dimensions were established: technical-constructive aspects, the socio-organizational aspect and, finally, the political and institutional aspects. This multidimensional approach seeks to identify the role of ownership in achieving and realizing the right to the city.

Durante los últimos veinte años, en la región se desarrollaron políticas públicas de mejoramiento barrial con el propósito de urbanizar asentamientos precarios. Sin embargo, estas intervenciones han afectado una masa relevante de pobladores para desarrollar plenamente su derecho a la ciudad. Por otra parte, son significativos los obstáculos que encuentran los pobladores para transitar estos procesos de manera apropiada, según términos de Lefebvre, como una condición de una producción justa y democrática.El presente texto reflexiona, a partir del trabajo de la asociación civil Proyecto Habitar, en alianza con la Defensoría General de la Nación Argentina durante 2018, sobre el papel que juega la apropiación en los procesos de urbanización que incluyen relocalización de población, específicamente en el barrio Villa Jardín del municipio de Lanús, Área Metropolitana de Buenos Aires, a partir de la implementación de una política pública de mejoramiento barrial. Para el análisis, se establecieron tres dimensiones: los aspectos técnico-constructivos, aspectos socio-organizacional y, por último, los aspectos políticos e institucionales. Con dicho abordaje multidimensional se busca identificar el papel que juega la apropiación para alcanzar y efectivizar el derecho a la ciudad.
Appropriation as a condition for the right to the city. The case of the neighbourhood improvement policy of Villa Jardín, Municipality of Lanús, Buenos Aires
Keywords: Right to the city; Appropriation; Relocalization; Inequality; Derecho a la ciudad; Apropiación; Relocalización; Desigualdad; https://purl.org/pe-repo/ocde/ford#6.04.08